Microbial Aromatization of Steroids into Equilin - Sehgal, S. N. (Appl Microbiol, 1970)
This report describes the bioconversion of 19-hydroxy-androsta-4, 7-diene-3, 17-dione into equilin with Nocardia rubra. Through mutation and improvement of medium and of conditions, the bioconversion could be improved to yield 40% equilin for a substrate concentration of 1 g/liter. Aromatization of several other 19-hydroxy and 19-nor substrates of the androstene series is reported, and the influence of various substitutions of the substrate molecule on aromatization is discussed.